2019
DOI: 10.3389/fnins.2019.00983
|View full text |Cite
|
Sign up to set email alerts
|

Adult Goat Retinal Neuronal Culture: Applications in Modeling Hyperglycemia

Abstract: Culture of adult neurons of the central nervous system (CNS) can provide a unique model system to explore neurodegenerative diseases. The CNS includes neurons and glia of the brain, spinal cord and retina. Neurons in the retina have the advantage of being the most accessible cells of the CNS, and can serve as a reliable mirror to the brain. Typically, primary cultures utilize fetal rodent neurons, but very rarely adult neurons from larger mammals. Here, we cultured primary retinal neurons isolated from adult g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Contactin-1 is a cell adhesion protein involved in axonal organization in early central nervous system development. 45 Retinal contactin-1 has been found to be downregulated following hyperglycemia, 46 indicating that contactin-1 is downregulated in retinal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Contactin-1 is a cell adhesion protein involved in axonal organization in early central nervous system development. 45 Retinal contactin-1 has been found to be downregulated following hyperglycemia, 46 indicating that contactin-1 is downregulated in retinal stress.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of our culture conditions revealed inverse differences in base media on their effects on cell survival versus the percentage of cells with neurite processes in RGCs and CD15 + neurons. The different base media differ by osmolarity ranking in osmotic concentration as N < NA < DN = DW < DNA [59,60]. RGCs and CD15 + cells exposed to lower osmolarity (N) increased in cell viability, contrary to adult hippocampal neuronal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This mildly lower rate of glucose metabolism was also explored in one study using Mecp2 null mice that demonstrated how impairment of enzymes such as voltage-dependent anion channel 3 (VDAC3) (abundant in the outer mitochondria membrane), cytochrome C oxidase subunit 5a (COX5a) (complex IV), NADH dehydrogenase-ubiquinone 1 beta subcomplex subunit 8 (NDUFB8) (Complex I), and ATP synthase F1 subunit β (ATP5B) (Complex V) in the respiratory complexes of neuronal mitochondria, resulted in significant redox imbalance [ 24 ]. Additionally, an in vitro study demonstrated that cultured retinal neurons from adult goats in a hyperglycemic condition (25 mM of glucose) compared to a normal condition (5 mM) for 10 days, grew with abnormal length [ 185 ]. A recent study proposed significantly increased expression of MeCP2 and HDAC1 in streptozotocin-induced hyperglycemic mice, suggesting a strong connection between glucose metabolism and MeCP2 [ 186 ].…”
Section: The Interplay Between Mecp2 and Brain Metabolismmentioning
confidence: 99%